PENGEMBANGAN EMODUL BERBASIS PROBLEM BASED LEARNING BERBANTUAN HEYZINE FLIPBOOK PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS V SEKOLAH DASAR - Pratiwi, Rifa; Fitria, Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The learning process in elementary schools is still predominantly teacher-centered and relies on limited teaching materials, such as printed books and worksheets, causing students to be less active and easily bored. The use of interactive digital teaching materials is also still minimal, which impacts students’ engagement and understanding, especially on the topic of the human respiratory system. Therefore, this study aims to develop a Problem Based Learning (PBL)-based e-module assisted by Heyzine Flipbook that meets the criteria of validity, practicality, and effectiveness for fifth-grade elementary school students. This research employed a Research and Development (R&D) method using the 4-D development model, which includes the stages of define, design, develop, and disseminate. The research instruments consisted of validation sheets, practicality questionnaires, and learning outcome tests in the form of pretest and posttest. The trial subjects consisted of fifth-grade students at SDN 11 Koto Marapak and SDN 07 Batang Kabung, while the research subjects were fifth-grade students at SDN 02 Talago Sariak. The validity test conducted by material, media, and language experts indicated that the e-module was very valid, with an average validation score of 94.67%. Based on the responses from teachers and students in the two trial schools, the e-module was categorized as very practical, with average scores of 96.25% and 98.05%, respectively. Meanwhile, the responses from teachers and students in the research school also showed that the e-module was very practical, with average scores of 97.5% and 98.6%, respectively. The effectiveness test in the two trial schools showed a result of 84.08% (effective category), while the research school showed 76.92% (effective category). Therefore, the Problem Based Learning-based e-module assisted by Heyzine Flipbook on the topic of the human respiratory system for fifth-grade elementary school students is considered very valid, very practical, and effective for use in learning.